On The Demand Dynamics of Electricity in Ghana: Do Exogenous Non-Economic Variables Count? - Ackah, Ishmael; Adu, Frank; Takyi, Richard Opoku (International Journal of Energy Economics and Policy, 2014)
The purpose of this study is to identify and quantify the effect of endogenous and exogenous economic factors on electricity demand in Ghana. The Structural Time Series Model is employed due to its ability to capture exogenous non-economic variables. The findings reveal that education has significant effect on electricity consumption in both the short and the long run. Education has inverse relationship with electricity consumption implying that the more consumers are educated, the less electricity they consume. The study also reveals that price changes have less impact on electricity consumption in the short run and that efficiency in electricity consumption has improved since 1971 and will continue for the next twenty years. The study recommends that more public education should be carried out to enhance energy conservation and also, realistic prices should be charge for electricity consumption to allow private investment into the sector. Keywords: electricity consumption; efficiency; economic factors JEL Classifications: Q43; Q49; O40